The Measures to Develop the Competence of Knowledge Manipulation in Real Life for Pupils through the System of Real Exercises with Metal Chemistry of Grade 12 - Nguyen Thi Kim Anh; Tran Anh Tuan (My University, 2018)
The Measures to Develop the Competence of Knowledge Manipulation in Real Life for Pupils through the System of Real Exercises with Metal Chemistry of Grade 12
Keywords: Knowledge manipulation